Targeting Adenosine Receptor by Polydeoxyribonucleotide: An Effective Therapeutic Strategy to Induce White-to-Brown Adipose Differentiation and to Curb Obesity - Federica Mannino; Giovanni Pallio; Alessandra Bitto; Domenica Altavilla; Letteria Minutoli; Violetta Squadrito; Vincenzo Arcoraci; Domenico Antonio Giorgi; Igor Pirrotta; Francesco Squadrito; Natasha Irrera (MDPI AG, 2021)
Obesity is a worldwide chronic metabolic disease characterized by an abnormal fat accumulation and represents one of the main risk factors for several diseases. White adipose tissue is the primary site for energy storage in the form of triglycerides, whereas brown adipose tissue does not store energy-providing lipids but rather dissipates it by producing heat. White-to-brown adipocyte trans-differentiation could represent a new target of anti-obesity strategies and result in fat reduction. Previous studies indicated that adenosine receptor activation induces trans-differentiation of white adipocytes to brown adipocytes. The aim of this study was to evaluate the effects of polydeoxyribonucleotide (PDRN), an A2Ar receptor agonist, in an in vitro model of browning. Mouse 3T3-L1 pre-adipocytes were differentiated in mature adipocytes with specific culture media and then treated with PDRN (10 µg/mL), PDRN + ZM241385 (1 µM), CGS21680 (1 µM) and CGS + ZM241385 for 24 h. Cell viability was studied by MTT assay, and browning induction was evaluated by Oil Red O staining and by RT-qPCR to study gene expression of browning markers. PDRN, as well as CGS21680, reduced the accumulation of lipids, cell volume and lipid droplet size; increased the expression of UCP1, PRDM16 and DIO2, considered as browning markers; and reduced the expression of FASn and FABP4, considered as whitening markers. In addition, PDRN decreased leptin expression and enhanced adiponectin mRNA levels. All these effects were abrogated when PDRN was co-incubated with the A2Ar antagonist ZM241385. In conclusion, these results suggest that PDRN is able to induce the white-to-brown adipose differentiation through A2Ar stimulation. Since PDRN is a safe drug already available in the market for other therapeutic indications, its "anti-obesity" potential warrants investigation in a clinical scenario.